Chronic spontaneous urticaria in pediatric age - Machado Cunha, Inês (2020)
Introduction: Chronic spontaneous urticaria is characterized by emergence of pruritic maculopapular cutaneous lesions recurring for more than six weeks, without known triggering factor. Association with autoimmunity is sometimes present, with urticaria preceding the onset of autoimmune disease. Clinical case: A five-year-old female with a personal history of allergic asthma and family history of thyroid disease was referred to the Immunoallergology consultation for cutaneous complaints compatible with urticaria with more than three years of evolution. Inducible urticaria forms were excluded. Analytical study revealed positive antinuclear antibodies with a 1/320 titer and positive basophil activation test after stimulation with autologous serum. Control of cutaneous manifestations was achieved with full dose antihistaminic H1. Conclusion: Chronic spontaneous urticaria associated with autoimmunity is rare in children. Clinical follow-up should be maintained to evaluate disease control and enable early recognition of other autoimmunity manifestations.